2003
DOI: 10.1046/j.1468-1331.2003.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Memory deficits and retrieval processes in ALS1

Abstract: Subtle neuropsychological deficits have been described in patients affected by amyotrophic lateral sclerosis (ALS) without dementia. Overall, selective impairment in memory function has been reported, but the source of memory impairment in ALS has yet to be defined. We performed neuropsychological screening in 20 ALS patients. Semantic encoding and post-encoding cue effects on the retrieval of word lists were investigated in the ALS patients and normal controls. Severity of memory impairment was correlated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 32 publications
6
58
0
2
Order By: Relevance
“…Because involvement of the perforant pathway has been considered to be one of the major lesions explaining contextual and episodic memory disturbance in AD [3], it is plausible that similar involvement of the perforant pathway, as we demonstrated in the present study, may explain similar memory deficits observed in some ALS patients with dementia. Currently, neuropsychological assessment of ALS patients with dementia is usually based on the assumption that cognitive abnormalities, including memory deficits, are related to frontal lobe dysfunction [20][21][22]. However, the present study indicates the possibility that the involvement of the perforant pathway is another candidate to explain cognitive dysfunction, especially memory deficits, sometimes found in ALS patients with dementia.…”
Section: Discussionmentioning
confidence: 51%
“…Because involvement of the perforant pathway has been considered to be one of the major lesions explaining contextual and episodic memory disturbance in AD [3], it is plausible that similar involvement of the perforant pathway, as we demonstrated in the present study, may explain similar memory deficits observed in some ALS patients with dementia. Currently, neuropsychological assessment of ALS patients with dementia is usually based on the assumption that cognitive abnormalities, including memory deficits, are related to frontal lobe dysfunction [20][21][22]. However, the present study indicates the possibility that the involvement of the perforant pathway is another candidate to explain cognitive dysfunction, especially memory deficits, sometimes found in ALS patients with dementia.…”
Section: Discussionmentioning
confidence: 51%
“…43 As for ALS, memory deficits have been controversial and most studies link memory impairment to executive dysfunction. 81,98,99 However, recent studies report authentic episodic memory deficits and implicate MTL structures, showing that memory impairment in non-demented ALS patients is not exclusively a disturbance of the executive functioning. 52,82,83,88,[100][101][102][103] Semantic memory Semantic memory is the knowledge of everyday objects and events and its loss is attributed to the deterioration of the ATL.…”
Section: Clinical/neuropsychological Findingsmentioning
confidence: 99%
“…Disorientation and symptoms of disinhibition were not as prominent until later in the illness. Impairment on test of language function (eg, animal fluency) and episodic memory recall (eg, word lists) have been widely reported in both ALS 24,30 and in FTD variants. [31][32][33] Furthermore, these results are consistent with findings of anterior temporal lobe atrophy which has been well documented in ALSFTD.…”
Section: Discussionmentioning
confidence: 99%